THE ROLE OF SHAPE AND COLOUR IN CREATING THE VISUAL IDENTITY OF FURNITURE (Innovation in Woodworking Industry and Engineering design, 2026)
The visual identity of a furniture piece allows it to stand out from others with similar func-tion. It makes it easily recognizable and memorable, which largely enhances its aesthetic qual-ities. Color and shape are two of its key elements.The paper examines visual identity, its basic components and the relationship between them. The participation of color and shape in visual identity formation for easily memorable furniture pieces is analyzed.